STUDY OF BATCH SCALE-UP BENTONITE ACTIVATION USING SULFURIC ACID - REZKY I. ANUGRAH (Indonesian Mining Journal, 2012)
As a commodity for industrial applications, bentonite is needed in a large number of tonnages. Indonesia retains about 6 hundred million tons of bentonite resources, but its quality does not yet satisfy industrial spesifi cation. Most Indonesian bentonite is calcium-bentonite type. Therefore, it is necessary to activate the material to en- hance its absorption ability for decolorizing crude palm oil in cooking oil industries. This research was aimed to obtain the optimal bleaching power in order to decolorize the crude palm oil effectively. The batch scale bentonite activation used raw material from Sarimanggu, Tasikmalaya district, West Java. Since 40 %-solid gave a better average bleaching power value than that of 20 %, the activation was then focused at seeking the best condition with regards to the activition time (hour) and reagent dosages (sulfuric acid). The batch up scale of this research refered to the use of a 100-kg bentonite as the feed. The feed size was -10 mesh. The use of sulfuric acid was2.5 to 20 % (equivalent to 0.13 to 1.02 N) for 20 % solid and 2.5 to 15 % (equivalent to 0.34 to 2.04 N) for 40 % solid. A series of activation times was 1, 2, 3, 4, and 5 hours. It started when sulfuric acid has been depleted. Sampling was completed for each hour when a sample was neutralized until pH = 7. The sample was dried and the rest of bentonite slurry was fl owed into a dilution tank to be neutralized using water. Condition of 1-hour activation and 7.5 %-sulfuric acid (equivalent to 1.02 N) provided the best bleaching power value (88 %).